2016
DOI: 10.1186/s12891-016-1060-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification in GRMD dog muscle of critical miRNAs involved in pathophysiology and effects associated with MuStem cell transplantation

Abstract: BackgroundDuchenne muscular dystrophy (DMD) is an X-linked muscle disease that leads to fibre necrosis and progressive paralysis. At present, DMD remains a lethal disease without any effective treatment, requiring a better understanding of the pathophysiological processes and comprehensive assessment of the newly identified therapeutic strategies. MicroRNAs including members of the muscle-specific myomiR family have been identified as being deregulated in muscle of DMD patients and in mdx mice used as a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
(23 reference statements)
0
7
0
2
Order By: Relevance
“…Over the past 6 years, several studies have demonstrated the clinical efficacy of MuStem cell treatment to repair muscle tissue, highlighting the potential of this muscle-derived stem cell population in cell-based therapies [ 53 56 ]. hMuStem cells have been previously isolated, expanded, and characterized using FBS-supplemented growth culture media [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 6 years, several studies have demonstrated the clinical efficacy of MuStem cell treatment to repair muscle tissue, highlighting the potential of this muscle-derived stem cell population in cell-based therapies [ 53 56 ]. hMuStem cells have been previously isolated, expanded, and characterized using FBS-supplemented growth culture media [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on their initial delayed adhesion properties, we isolated and characterized a population of adult stem cells (named MuStem cells) from healthy dog skeletal muscle, and demonstrated their efficacy following vascular delivery into the clinically relevant dog model of Duchenne muscular dystrophy (DMD), in which we observed persistent clinical stabilization and significant muscle repair [ 53 56 ]. More recently, we isolated and extensively characterized the human counterparts of these cells (hMuStem cells), and demonstrated their regenerative ability when delivered into injured muscle [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through signaling mediated by several biological pathways, MuStem cell implantation limits the progression of muscle damage and stabilizes the clinical status of recipient dogs. 29 , 30 , 31 More recently, we isolated the human counterpart of MuStem cells (hMuStem cells), for which we have demonstrated comparably robust muscular-regeneration capacity after delivery into injured skeletal muscle in immunodeficient mice. 32 These compelling findings point to hMuStem cells as attractive candidates for the treatment of skeletal muscle diseases.…”
Section: Introductionmentioning
confidence: 99%
“…No homem, os sintomas clínicos são demonstrados de forma dinâmica, afetando o músculo estriado esquelético, músculo liso e músculo cardíaco (BROLIO et al, 2014;MARKHAM et al, 2017). Por se tratar de uma doença de caráter congênito, as manifestações clínicas da doença aparecem desde o início da infância e surgem com maior evidência entre três e cinco anos de idade (ARAUJO et al, 2017 (ROBRIQUET et al, 2016;SCHNEIDER et al, 2018).…”
Section: Introductionunclassified
“…observada melhora clínica nos cães afetados(ROBRIQUET et al, 2016; COENEN-STASS; WOOD; ROBERTS, 2017).Outro estudo com terapia gênica demonstrou que cães GRMD com quatro dias de idade que receberam a injeção intravenosa de um vetor associado ao adenovírus (AAV9) carreando um códon humano com o mini-gene da distrofina sob influência do citomegalovírus (CMV), exibiram expressão muscular generalizada do transgene posteriormente a 16 semanas de tratamento, entretanto sem implicações clínicas satisfatórias(FRAYSSE et al, 2017; KORNEGAY, 2017;LE GUINER et al, 2017; VOIT et al, 2017).…”
unclassified